Evidence for objects of implementation in healthcare: considerations for Implementation Science and Implementation Science Communications - Wensing, Michel; Sales, Anne; Aarons, Gregory A.; Xu, Dong (Roman); Wilson, Paul (Implementation science, 2022)
The journals Implementation Science and Implementation Science Communications are focused on the implementation of evidence into healthcare practice and policy. This editorial offers reflections on how we handle this as editors. Studies that focus on the simultaneous implementation of implementation objects and (technological or other) structures to enable their implementation are considered on a case-by-case basis regarding their contribution to implementation science. Studies on implementation objects with limited, mixed, or of out-of-context evidence are considered if the evidence for key components of the object of interest is sufficiently robust. We follow GRADE principles in our assessment of the certainty of research findings for health-related interventions in individuals. Adapted thresholds apply to evidence for population health interventions, organizational changes, health reforms, health policy innovations, and medical devices. The added value of a study to the field of implementation science remains of central interest for our journals.